Strategi Pengelolaan ZIS secara Produktif dalam Rangka Pemberdayaan Ekonomi Umat - Lutfi Abdul Ghani; Dewi Rahmi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The purpose of this study is to determine the strengths and weaknesses in the management of productive ZIS in PZU Bandung. Knowing the opportunity and threat factors in the management of productive ZIS in PZU Bandung. Knowing the effective utilization strategy of productive ZIS in the framework of economic empowerment of the people in PZU Bandung. Qualitative research methods that produce descriptive and written data with information from related institutions in the object of research using SWOT analysis. The approach uses field research and interviews as tools to obtain more detailed and reliable data. The results showed that the strength factor of the SWOT analysis results in the management of productive ZIS in PZU Bandung is the management, services and facilities provided, to the promotion. While the weakness is the lack of amil and knowledge of the use of digital information systems in improving online services. The opportunity factors of the SWOT results are the strategic location of PZU Bandung and the establishment of cooperation with other institutions, while the threat is the lack of mustahik knowledge in the management of aid funds and the decrease in the amount of ZIS funds received and the limited implementation of several programs during the covid-19 pandemic. The strategy obtained in this study is to continue to improve and develop the quality and quantity of amyl. Abstrak. Tujuan penelitian ini adalah mengetahui faktor kekuatan dan kelemahan dalam pengelolaan ZIS produktif di PZU Bandung. Mengetahui faktor peluang dan ancaman dalam pengelolaan ZIS produktif di PZU Bandung. Mengetahui strategi pendayagunaan ZIS produktif yang efektif dalam rangka pemberdaraan ekonomi umat pada PZU Bandung. Metode penelitian kualitatif yang menghasilkan data deskriptif dan tertulis dengan informasi dari lembaga terkait dalam objek penelitian menggunakan analisis SWOT. Pendekatan menggunakan penelitian lapangan dan wawancara sebagai alat bantu untuk mendapatkan data yang lebih detail dan terpercaya. Hasil penelitian menunjukkan bahwa faktor kekuatan dari hasil analisis SWOT dalam pengelolaan ZIS produktif di PZU Bandung yaitu pengelolaan, pelayanan dan fasilitas yang disediakan, hingga bagian promosi. Kelemahanmya yaitu kurangnya jumlah amil serta pengetahuan penggunaan sitem informasi digital dalam peningkatan layanan online. Faktor peluang dari hasil SWOT yaitu lokasi PZU Bandung yang strategis dan kerjasama dengan lembaga lain, sedangkan ancamannya adalah kurangnya pengetahuan mustahik dalam pengelolaan dana bantuan dan penerununan jumlah dana ZIS yang diterima dan keterbatasan pelaksanaan beberapa program di masa pandemi covid-19. Strategi yang diperoleh dalam penelitian ini adalah dengan terus meningkatkan dan mengembangkan kualitas serta kuantitas amil.